ROLE OF AUXIN AND DATES OF PLANTING ON GROWTH OF TES OF PLANTING ON GROWTH OF CUTTING RAISED PLANTLETS OF PHALSA (GREWIA ASIATICA L.) - PARSHANT BAKSHI, JYOTI DEVI,; NIRMAL SHARMA, V. K. WALI, KIRAN KOUR (The Bioscan, 2016)
The results of the present investigation which was conducted under irrigated conditions at Research Farm, Division of Fruit Science, Faculty of Agriculture, Udheywalla, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu with the objective to find out optimum concentration of growth regulators and suitable planting time for the Phalsa (Grewia asiatica L.) by the means of vegetative propagation through cuttings revealed that phalsa cuttings treated with IBA 300 ppm and planted on 30th July showed highest growth and shoot development characters. Per cent survival (63.66 %) was highest in cuttings planted on 30 thy July, while mean number of leaves (18.74), leaf area (3.76 cm2 ) and chlorophyll content (39.76%) were found to be highest when the cuttings were treated with IBA 300 ppm. Also, fresh and dry weight per leaf (3.59 g and 2.68 g, respectively) and partitioning coefficient of leaves (20.98%) showed its superiority when the planting was done on 30th July indicating the most appropriate time for obtaining maximum success from phalsa cuttings